Determination of the Permeation and Penetration of Flurbiprofen into Cadaveric Human Pharynx Tissue - Turner R; Wevrett SR; Edmunds S; Brown MB; Atkinson R; Adegoke O; Kulasekaran A; Shea T (Dove Medical Press, 2020)
Rob Turner,1 Sean Robert Wevrett,1 Suzanne Edmunds,1 Marc B Brown,1,2 Robert Atkinson,3 Oluwajoba Adegoke,3 Anuradha Kulasekaran,4 Tim Shea5 1MedPharm Ltd, Surrey Research Park, Guildford, UK; 2The Research Centre in Topical Drug Delivery and Toxicology (TDDT), University of Hertfordshire, College Lane Campus, Herts, UK; 3Medical Science, Reckitt Benckiser, Hull, UK; 4Medical Affairs, Reckitt Benckiser, Slough, UK; 5Medical Science, Reckitt Benckiser, Parsippany, NJ, USACorrespondence: Anuradha KulasekaranReckitt Benckiser PLC, 103– 105 Bath Road, Slough SL1 3UH, UKTel +44 1753 217800Email anuradha.kulasekaran@rb.comObjective: Flurbiprofen 8.75 mg spray and lozenge have a rapid onset of action for sore throat relief, suggesting local action, although tissue penetration and the mechanism of local relief have not been determined. This investigation aimed to quantify the permeation and penetration of flurbiprofen, applied as local pharmaceutical forms, into full-thickness cadaveric human mucosal pharynx tissue, representing the clinical scenario as far as possible.Methods: A validated high-performance liquid chromatography method quantified the permeation and penetration of flurbiprofen (spray and lozenge formulations) into human cadaveric pharynx tissue using a micro Franz cell model mimicking physiological and anatomical conditions. Full-thickness mucosal pharynx tissue, consisting of oral epithelium, basement membrane, and lamina propria, was utilized to imitate the in vivo setting. Flurbiprofen was analyzed on the surface of the pharynx tissue, within the pharynx tissue and in receiver fluid, over 60 mins.Results: Flurbiprofen was detected in receiver fluid from 10 mins following spray application and was quantifiable from 20 mins. Flurbiprofen from lozenge was detected from 10 mins and was above the limit of quantitation in receiver fluid from 40 mins. Flurbiprofen recovered from the surface of the pharynx tissue was 24.45% and 8.48% of applied dose for spray and lozenge, respectively. Flurbiprofen recovered within pharynx tissue was 46.50% and 54.65% of applied dose for spray and lozenge, respectively. For flurbiprofen lozenge, recovery within pharynx tissue was 6-fold higher relative to recovery from the pharynx tissue surface.Conclusion: Flurbiprofen from spray and lozenge formulations penetrated human cadaveric pharynx tissue, indicating that flurbiprofen can reach all layers of the pharynx mucosal tissue, including the underlying lamina propria, which contains blood vessels and nerve fibers that contribute to pain during sore throat. This suggests that flurbiprofen may have a local mechanism of action for sore throat, although this has yet to be determined.Keywords: chromatography, high-pressure liquid, flurbiprofen, Franz diffusion cell, pharynx